A multifunctional oxidative stress nanoamplifier with ROS amplification and GSH exhaustion for enhanced chemodynamic therapy - Zhong, Wenzhao; Guo, Feng; Chen, Fangman; Law, Man-Kay; Lu, Jun; Shao, Dan; Yu, Hua; Chan, Ging; Chen, Meiwan (Frontiers in Pharmacology, 2022)
Chemodynamic therapy (CDT) eradicates tumors by intratumoral catalytic chemical reaction and subsequently disrupts redox homeostasis, which shows tumor specific reactive oxygen species (ROS)-mediated therapy. However, insufficient ROS generation and high levels of glutathione (GSH) in cancer cells have limited the therapeutic efficacy of CDT. Herein, we constructed a multifunctional oxidative stress nanoamplifier with ROS amplification and GSH exhaustion for enhanced CDT. Such a sandwich-like nanoamplifier comprised layer-by-layer artesunate (AS) and calcium carbonate coatings on the surface of manganese dioxide (MnO2) nanoparticles. The nanoamplifier was disassembled under an acidic environment once accumulated into tumor sites, and subsequently released AS to replenish the intratumoral peroxide pool for ROS amplification. Besides being an AS carrier, MnO2 exhausted GSH to yield Mn2+ ions that catalyzed the overexpression of H2O2 in the tumor, further intensifying the oxidative stress and facilitating cancer cell death. Taken together, our findings not only provide a paradigm for fabricating intratumoral catalytic nanomaterials, but also present a new ROS enhancement strategy to improve anti-tumor efficacy. Our multifunctional oxidative stress nanoamplifier might broaden the future of CDT.